Comparative evaluation of sonicated shrimp waste hydrolysates as potential fertilizers for legumes (2019)
ABSTRACT: The global annual production of shrimp is nearly 4.8 million metric tons, generating almost half this weight in waste. The aim of this study was to assess the development and crop production of legumes fertilized with alkaline sonicated shrimp waste under greenhouse conditions. Plants were grown separately under the following fertilization regimes: untreated soil, untreated cotton substrate, two commercial fertilizers [commercial organic fertilizer (COF) and commercial synthetic fertilizer (CSF)], and shrimp waste having hydrolysis degrees of 0%, 15%, 18%, and 25%. Electrical conductivity of shrimp-based fertilizers (SBFs) decreased with hydrolysis degree. However, pH (6.7–6.9), densification (0.2–0.3 g·cm–3) and conductivity (10–21 mS·cm–1) of soil was unaffected by fertilization. Furthermore, CSF had the greatest ionic exchange capability. Sonolysis resulted in an assimilable source of C, N, and O, mainly derived from carbohydrates and proteins, and increased the availability of minerals such as Ca and phosphate. The greatest plant growth in both legumes was achieved when treated with CSF, whereas the raw shrimp waste caused a beneficial plant growth and crop yield mainly for Phaseolus vulgaris. All fertilizers showed typical type II isotherms, and soil substrate per se exhibited the largest water uptake. The soil microbiota increased during the growing cycle and then decreased as the reproductive phase started. In fact, soil planted with Phaseolus vulgaris showed a greater microbial population than Pisium sativum. These shrimp waste hydrolysates can be used as alternative organic soil fertilizers and are suggested as substitutes for synthetic fertilizers.